Strategi Pengembangan Agrowisata Kopi Di Desa Wisata Tempur Kabupaten Jepara - Prasetyo, Yudhiet Nur; Adikampana, I Made (JURNAL DESTINASI PARIWISATA, 2021)
This research explains about coffee agrotourism developing strategy in Tempur Village, Keling, Jepara, Central Java. The main potential of this village is coffee products, but these coffee products are only for souvenirs and there are no plans to develop it as an agrotourism. Looking back at this issue, it needs to do a deep research on developing coffee agrotourism so it will be a good product from this village. This research is focused on analyzing agrotourism developing plans, especially coffee estate which has not developed yet in this village. This research has two scopes which are limited by two variables, the first one is the existing condition of Tempur Village including profile, potential, and tourism product component, the second one is developing village potential including coffee agrotourism developing strategy using SWOT (Atraction, Aminities, Accessibilitiy, Ancelery) analysis. The result of this research explains that Tempur Village has a potential to be developed as coffee agrotourism, because this region has fertile soil, large coffee estate and natural environment. In developing coffee agrotourism needs good preparation from the government, coffee farmers, and also local residents so it will be in harmony. Coffee farmers empowerment, local residents and attractive coffee product packaging production needs to be taught in developing coffee agrotourism. Furthermore, upgrading village facilities to reach the tourism destination needs to be done to support tourism development, so the plans which have been planned can run well. With the plans of coffee agrotourism development, it is hoped to be useful for academics and the government in order to increase science. Keyword: Strategy of Developing Coffe Agrotourism.